SISTEM PENGELOLAAN KAYU MANIS DI DESA LOKLAHUNG, KECAMATAN LOKSADO, KALIMANTAN SELATAN - Vennireza Salsabella; Hafizianor -; Setia Budi Peran (Universitas Lambung Mangkurat, 2021)
This study aims to examine the management system of cinnamon by Loklahung village community, Loksado sub-district, South Kalimantan. The method used in this research is quantitative and qualitative approaches. Quantitative approach using questionnaires and observations. While the qualitative approach seeks understanding by using participant observation, open interviews, interviews with key informants and study documents / libraries. Data sources used are primary data and secondary data. Primary data is data obtained directly in the field. While secondary data is data obtained by analyzing, collecting and studying books and supporting literature as reference material. Based on the results of the study, it is known that as many as 90.8% of Loklahung villagers own cinnamon gardens and manage their own cinnamon gardens from land preparation, planting, maintenance to harvesting cinnamon. People plant cinnamon on the same land with rice and after harvesting rice using a monoculture system and intercropping with fruit and vegetable commodities. Cinnamon maintenance includes stitching, fertilizing and weeding. Harvesting or taking cinnamon bark through several stages, that are choosing a tree to be cut down, cutting down trees, gnawing and skinning trees. Cinnamon harvests in the form of rolls are then sold to collectors or middlemen at a price of IDR 50,000.00 / kg.Keywords: Management syste; Garden; cinnamon